PROSESI TRADISI LARUNGAN DALAM PENDIDIKAN KARAKTER ANAK - Rofiah, Neneng Chalimatur; Fajrie, Nur; Rondli, Wawan Shokib (Jurnal Tunas Pendidikan, 2023)
This study aims to describe the meaning of education on the Larungan tradition for character education for children in Ujung Batu Jepara village. The Larungan Tradition procession in Ujung Batu Jepara village begins with the slaughter of a buffalo at the Slaughterhouse (RPH) in Jobokuto Village, then the buffalo meat is distributed to residents in Ujungbatu Village and the buffalo head is floated into the sea as a symbol of getting rid of ignorance, after which it is continued with a pilgrimage to the grave Ms. Lanang after asar time, and a pilgrimage to Mbah Ronggo Mulya's grave after maghrib time. Then proceed with the shadow puppet show. The following day a ceremony of throwing the buffalo head into the sea was led by local religious leaders and attended by personnel from elements of the Jepara Regency Government, Ujungbatu Village Government, community leaders and other members of the community. The character values contained in the Larungan Tradition in Ujung Batu Jepara village include religion, tolerance, hard work, democracy, love for the motherland and social care.